AN INTEGRATED FUZZY ANP-FUZZY DEMATEL-FUZZY MULTI-OBJECTIVE LINEAR PROGRAMMING APPROACH FOR WEAPON SYSTEMS ACQUISITION - Rostamkhani, Ramin; Abbasi, Morteza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Weapon systems selection is one of the most crucial steps of a successful weapon systems acquisition process. The weapon systems selection problem is a complex decision-making problem involving multiple objectives and multiple interactive factors. This study presents a novel integrated approach to the weapon systems portfolio selection problem. The proposed integrated approach combines fuzzy decision-making trial and evaluation laboratory (DEMATEL), fuzzy analytic network process (ANP), and fuzzy multi-objective linear programming (FMOLP). The integrated fuzzy DEMATEL-fuzzy ANP method is firstly applied to identify the weights of the criteria, and FMOLP is then used to determine the optimal weapon systems portfolio. Capabilities-based assessment (CBA) results and the traditional weapon system selection criteria are considered in the proposed approach, which yields a comprehensive set of criteria ranging from technological aspects to the factors identified through CBA. Furthermore, functional constraints are taken into account in the FMOLP phase of the procedure. Finally, the proposed approach is applied to a real-size problem to show its applicability and practicality.